2012
DOI: 10.1039/c1cc14379d
|View full text |Cite
|
Sign up to set email alerts
|

Highly enantioselective Friedel–Crafts alkylation reaction catalyzed by rosin-derived tertiary amine–thiourea: synthesis of modified chromanes with anticancer potency

Abstract: We present herein for the first time the synthesis and preliminary biological evaluation of various modified chromanes via a rosin-derived tertiary amine-thiourea-catalyzed highly enantioselective Friedel-Crafts alkylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The α‐carbon atom of naphthols might be activated by an interaction between the adjoining tertiary amine scaffold of this catalyst and the hydroxy group in naphthols, together with β,γ‐unsaturated α‐ketoester derivatives were fixed and activated by the two thiourea hydrogen atoms through weak hydrogen bonds. Successively, the attack of the incoming nucleophiles to the Si ‐face of β,γ‐unsaturated α‐ketoester derivatives happen and then endures a hemiketal cyclization reaction to give corresponding product, that is consistent with the experimental consequences …”
Section: Organocatalyzed Asymmetric Friedel‐crafts Reactions Usingsupporting
confidence: 79%
See 1 more Smart Citation
“…The α‐carbon atom of naphthols might be activated by an interaction between the adjoining tertiary amine scaffold of this catalyst and the hydroxy group in naphthols, together with β,γ‐unsaturated α‐ketoester derivatives were fixed and activated by the two thiourea hydrogen atoms through weak hydrogen bonds. Successively, the attack of the incoming nucleophiles to the Si ‐face of β,γ‐unsaturated α‐ketoester derivatives happen and then endures a hemiketal cyclization reaction to give corresponding product, that is consistent with the experimental consequences …”
Section: Organocatalyzed Asymmetric Friedel‐crafts Reactions Usingsupporting
confidence: 79%
“…Furthermore, the transformations using 143 have been tested. Pleasantly, all reactions gave the opposite enantiomeric products with moderate yields and moderate to high ee s (Scheme , Table ) …”
Section: Organocatalyzed Asymmetric Friedel‐crafts Reactions Usingmentioning
confidence: 99%
“…developed a Friedel–Crafts alkylation of 1‐ or 2‐naphthols and β,γ‐unsaturated α‐keto esters. A chiral rosin‐derived thiourea catalyst 271 is deployed and the corresponding chromones are accomplished in good yields and excellent ee values (Scheme ) 301…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…A chiral rosin-derived thiourea catalyst 271 is deployed and the corresponding chromones are accomplished in good yields and excellent ee values (Scheme 159). [301] Substrates bearing cumulated double bonds are highly reactive and consequently interesting starting compounds for organocatalytic transformations. In this context Fu et al demonstrated their convenience for g-additions of malo-nates to allenoates and Weinreb allenamides.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Rosin-derived bifunctional thiourea organocatalysts, originated from the abundantly available natural rosin, were revealed to be highly efficient for some catalytic asymmetric reactions, including Aza-Henry [28], Mannich reaction [29,30], Aldol reaction [31,32], Michael addition [33][34][35][36], and Friedel-Crafts alkylation [37]. The thiourea moiety of those organocatalysts is usually introduced at position C-4 of rosin skeleton, while the tertiary amine moiety is either 1,2-diaminocyclohexane 1 or cinchona alkaloid 2 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%